The Global Research Trend in Information Governance - Muhtar, Entang Adhy; Candradewini, Candradewini; Rusli, Budiman; Karlina, Nina; Muharam, Riki Satia (UI Scholars Hub, 2023)
The word “governance” has gained extensive usage in the business sector. Thus, “information governance” is not a new addition to the lexicon. This study aims to examine English articles on information governance written by international academics and published in Scopus-indexed journals by adopting bibliometric and content analyses. We conducted the content analysis using the VOSviewer program, which allows us to display keyword co-occurrence and bibliographic coupling of nations and sources. We identified 587 publications on information governance spanning the last 30 years. The most prolific publication platform is the Journal of the American Health Information Management Association (n=32). The most productive nation is the United Kingdom (n=206). Citations reveal that the most significant authors and periodicals are Michie S. et al. (n=352) and the Journal of Medical Internet Research (n=552), respectively. The search terms for information governance (e.g., information governance, humans, and human) in this study generate six clusters. Research on information governance has experienced dramatic growth over the past three decades, which is evident from a worldwide viewpoint. Publications in European-published journals are observed. Consequently, Asia has to engage more actively in the study of this subject.